Plan estratégico de mejoramiento del programa de medicina prepagada Ecuasanitas S.A., basado en la satisfacción del cliente, en el Distrito Metropolitano de Quito. - Veintimilla Portilla, Ronald David (2014)
This work consists of three chapters, which elucidate the steps necessary to establish a model based on customer satisfaction strategic plan and how to apply this model to Ecuasanitas S.A. Company. For empty the investigation, we covers the theoretical framework with concepts and steps for understanding and developing a detailed strategic plan. Moreover, the concept of Prepaid Medicine is introduced with the intent learning the environment in which the company functions. To continue the study, an analysis of the company Ecuasanitas SA is preformed derived from the theory presented in part one. To begin an evaluation of the external factors directly influencing company’s development in Ecuador are assessed. Likewise, an internal study focused on gauging the company’s capabilities. Here various research and management tools for data collection are used to measure the company’s adequacy.